The political economy of molecules: vital epistemics, desiring machines and assemblage thinking. Issue 1 (2nd January 2020) - Elbe, Stefan; Long, Christopher
Abstract: Could the most miniscule of objects, imperceptible to the human eye, enact whole new political economies? The suggestion may seem odd, but this article shows that tiny molecules are already engendering new regimes of value across the fields of global health and biodefense. Delving genealogically into the onto-epistemology of the life sciences, the article thus traces the protracted molecular reconfigurations of state-market relations underpinning the global bioeconomy and civilian biodefense today. Using methodological precepts developed through assemblage thinking, this evolving patchwork of new constellations is conceptualized as a global molecular assemblage. Attending to the lively play of molecules in the world advances the post-Foucauldian, molecular study of biopolitics by exploring how scientific shifts in our 'vital epistemics' contour state-market relations. It further contributes to the development of a post-human international political economy that is more sensitive to the ways in which artefacts (like molecules) too exhibit particular kinds of 'agency' and 'force' in the world. Finally, it also enhances the field's ability to make unconventional, hitherto overlooked and multi-scalar connections in the study of political economy through the creative use of assemblage thinking. In the case of molecules, such assemblage thinking can – quite literally – reveal the value of 'life'.